2012
DOI: 10.1007/s12262-012-0722-2
|View full text |Cite
|
Sign up to set email alerts
|

Management of Bile Duct Injury at Various Stages of Presentation: Experience from a Tertiary Care Centre

Abstract: The clinical presentation, management and outcome of all patients with bile duct injury who presented to our tertiary care centre at various stages after cholecystectomy were analyzed. The patients were categorized into three groups: group A-patients in whom the injury was detected during cholecystectomy, group B-patients who presented within 2 weeks of cholecystectomy and group C-patients who presented after 2 weeks of cholecystectomy. Our team acted as rescue surgeons and performed 'on-table' repair for inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…Usually, there is delay in diagnosis. In these patients, cholangitis is the leading symptom of presentation (52,53).…”
Section: B) What Are the Symptoms And Signs Of Biliary Injury?mentioning
confidence: 99%
“…Usually, there is delay in diagnosis. In these patients, cholangitis is the leading symptom of presentation (52,53).…”
Section: B) What Are the Symptoms And Signs Of Biliary Injury?mentioning
confidence: 99%
“…Our results are consistent with other studies done in various centers of India. [5][6][7] Mean age of our patients was 47.6 years with male female ratio of 8:24. There are various conditions associated with increased risk of bile duct injuries such as acute cholecystitis, acute pancreatitis, cholangitis, scarring of Calot's triangle, intraoperative bleeding and anatomical variations.…”
Section: Discussionmentioning
confidence: 96%
“…6 Early repair is usually associated with high failure rates. 15,16 Two of our patient in group II and 14 in Group III were managed with delayed repair.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Ibrarullah et al reported their management of bile duct injuries at various stages of presentation. In case of bile leakage with intact common bile duct, an endoscopic sphincterotomy with insertion of a 10 Fr plastic stent was always performed 10 . If the biliary plastic stent is placed close to the origin of the leak, this may cause contamination of the abdominal cavity as mentioned earlier.…”
Section: Discussionmentioning
confidence: 99%